2018
DOI: 10.1159/000486905
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hypertension in Renal Transplant Recipients in Four Independent Cross-Sectional Analyses

Abstract: Background/Aims: This retrospective study analysed hypertension management and adherence to blood pressure (BP) targets among renal transplant recipients (RTRs) under specialized care in the Outpatient Transplantation Unit in the Department of Nephrology, Transplantology and Internal Medicine at Gdansk University Hospital. Methods: Medical records of 101, 316, 639 and 818 RTRs diagnosed with hypertension, who received outpatient care in 2001, 2006, 2011 and 2014, respectively were analysed in four independent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…In the present study, we analyzed data from our transplant center and divided patients into four groups based on the number of different antihypertensive drugs. The distribution of main antihypertensives used in our cohort was comparable to that of other transplant studies [13]. Our data showed that the number of different antihypertensives of KTx recipients is a strong predictor of poor allograft function and survival.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In the present study, we analyzed data from our transplant center and divided patients into four groups based on the number of different antihypertensive drugs. The distribution of main antihypertensives used in our cohort was comparable to that of other transplant studies [13]. Our data showed that the number of different antihypertensives of KTx recipients is a strong predictor of poor allograft function and survival.…”
Section: Discussionsupporting
confidence: 84%
“…However, multivariable Cox regression could not confirm beta-blockers as a risk factor for reduced death-censored allograft survival. Although they are the most frequently used antihypertensive agents after KTx in our cohort as well as in others [13,33], data on their influence on the outcomes of renal allograft outcome is scarce. Their frequent usage might be related to a high percentage of patients with chronic heart failure and/or arrhythmias as atrial fibrillation in the KTx patient collective [18,19].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…In this review, we focus on antihypertensive medications and briefly review bilateral native nephrectomy and RDN of native kidneys. (135). Beta-blockers were the most common antihypertensive medication used in this cohort followed by calcium channel blockers.…”
Section: Blood Pressure Managementmentioning
confidence: 85%
“…The cardioprotective effects and survival benefit of beta-blockers make them a favored medication in the general (161) and ESRD populations (162)(163)(164)(165). In kidney transplant recipients, a recent retrospective study from 2001 to 2014 showed that betablockers are the most common used antihypertensive medication (135). In addition, Aftab et al (166) conducted a single center retrospective study in 321 kidney transplant recipients over a 10 ± 4 year follow-up period and found that those who took beta-blockers had a significant survival advantage compared to those who did not.…”
Section: Beta-blockersmentioning
confidence: 99%